Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kompetisi Guru di Madrasah Aliyah NWDI Wakan: Human Resource Management in Improving Teacher Competence at NWDI Wakan Madrasah - Muhamad Zaril Gapari (Pendidikan Al-Gafari, 2026)
Human resources (HR), especially teachers, are a key factor in the success of educational institutions. However, based on initial observations at Madrasah Aliyah NWDI Wakan, various problems were found, such as a shortage of teaching staff, a mismatch between teacher competencies and their teaching fields, low discipline, and minimal use of learning media. Therefore, this study aims to describe how HR management is carried out to improve teacher competency through the recruitment, selection, and training and development processes. This study used a descriptive qualitative approach with data collection techniques such as observation, interviews, and documentation. The results showed that HR management at the madrasah has been carried out using a phased approach through internal selection, intensive coaching, and ongoing training, although various obstacles remain, such as budget limitations and a lack of formal training.